Muslim states and Syrian refugees: the Islamic perspective - Eishan Jan, Mohammad Naqib (2016)
This paper discusses the plight of the Syrian refugees and the responsibility of the Muslim states, especially the rich ones in the region, to grant the desperate Syrians asylum and protection. This responsibility emanates from the Islamic legal principles, as enshrined in the two primary sources of Islamic law, namely the Holy Quran and the Sunnah of the Prophet (pbuh). Other sources of Islamic law will also be referred to strengthen the argument that Muslim states have moral, religious and even legal obligation in Islam to provide the necessary protection to refugees in general and the Syrian refugees in particular. Had these states fulfilled their obligation vis-a vis refugees, the Syrian asylum seekers could have not risked their life to use the dangerous sea routs to seek asylum and protection in the European states.